Responsive lanthanide-doped nanoparticles for bioimaging - Yuan, D (2023)
With recent advances in nanotechnology, the tailored synthesis of functional nanoparticles has emerged as a new frontier for biomedical diagnostics, especially in the field of (pre-)clinical bioimaging. In this thesis, biocompatible superparamagnetic iron oxide nanoparticles (SPIONs) and Gd3+-doped mesoporous silica nanoparticles (Gd-MSNs) have been investigated as versatile, stimuli-responsive magnetic resonance imaging (MRI) contrast agents (CAs). One of the principal aims was to optimise T1 relaxivities (r1) for these paramagnetic nanoparticles, with a distinct emphasis on exploiting the often overlooked outer-sphere (OS) relaxation pathway. Another key objective was to design T1-active CAs whose OS relaxivities could be tuned in response to biologically-relevant stimuli (e.g., environmental pH), enabling disease-specific reporting capability by MRI. Following an introduction to the fundamental theory/project aims in Chapter 1, and a discussion of detailed synthetic/characterisation procedures (Chapter 2), the research results are presented in Chapters 3, 4 and 5. In Chapter 3, strategies for enhancing T1 contrast using Gd-MSNs are discussed. This enhancement is achieved by incorporating strong hydrogen-bonding acceptors (HBAs) into the channel sidewalls, influencing the mobility of the internalised water and hence amplifying OS relaxivities. This chapter also introduces a novel, one-pot Ugi-coupling reaction for the synthesis of bifunctional MSNs with dual-modal MRI and fluorescence imaging capabilities. In Chapter 4 it is shown that externally grafting a pH-responsive, hydrophilic polymer onto Gd-MSNs results in a powerful T1 contrast agent which possesses the highest reported r1 switches at clinically-relevant magnetic fields (1.4 T, 1.5 T and 3 T). These ultrahigh switches result from modulating the mobility of nanoconfined water, and consequently the OS relaxivities, through a conformational change of the polymer. Building on this polymer-mediated OS mechanism, Chapter 5 describes polymer-modified SPIONs possessing significant, reversible r1 switching, along with antifouling characteristics. Chapter 6 summarises the conclusions from Chapters 3 - 5. Chapters 7 and 8 provide relevant supplementary information and a list of references.